Investigation of three dimensional empirical indoor path loss models for femtocell networks - Zyoud, Al-Hareth; Chebil, Jalel; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Lwas, A.K. (2013)
Femtocell which is a home access point that installed by end consumers inside their houses is an important parameter and a promising technology in future wireless networks. It was proposed as a solution to the indoor propagation problems and to increase the indoor bandwidth. However, many challenges need to be addressed before deployment of femtocell. One of these challenges is the indoor propagation. Most of the available models are for long range communication like macro and micro cellular networks. Models for femtocell networks where the effects of walls and floors are appeared are necessary. In this paper eight different models of indoor propagation were studied and compared with measured data. Measurements were conducted in three story building. Four different scenarios with different numbers of penetrated walls and floors were considered. The results were statistical analysed by calculating the average error and the error standard deviation.